Unusual Cause of Severe Knee Pain - Lamichhane, J; Vaidya, B; Bista, P (Journal of Nepal Health Research Council, 2011)
MRI is the preferred modality to investigate seizure as diagnostic yield is higher and more specific due to its varied applications. Total of 160 brain MR images of patients suffering from seizure during one year period was evaluated. All seizure cases underwent specific protocol for imaging that targeted hippocampal/mesial temporal lobe imaging.